Advanced production routes for metal matrix composites. Issue 5 (15th November 2020) - Mussatto, Andre; Ahad, Inam UI; Mousavian, Reza Taherzadeh; Delaure, Yan; Brabazon, Dermot
Abstract: The use of metal matrix composites (MMCs) in a variety of products is significantly increasing with time due to the fact that their properties can be tailored and designed to suit specific applications. However, the future usage of MMC products is very much dependent on their beneficial aspects and hence it is critical to ensure in a robust repeatable manner the superior physical property advantages compared to conventional unreinforced monolithic metal counterparts. Although numerous routes are available for production of MMC products, each of them has their own advantages and disadvantages. This article provides an overview of advanced production routes for MMCs. The discussion also highlights challenges and presents a future prospectus for MMCs. Powder metallurgy and casting routes are still extensively used for production of MMCs. Aluminum alloys are today the most commonly used matrix materials in MMC products. Carbides (eg, SiC, TiC, and B4 C), carbon allotropes (eg, CNTs and graphene), and alumina (Al2 O3) are currently the most used reinforcement materials. Nevertheless, the use of nano and of hybrid reinforcements are seeing increased usage in niche applications. Additive manufacturing (AM) is discussed as a novel production route for MMC products. This process represents a promising method for the production of MMC products. Abstract : Overview flowchart of the processing steps involved during production of a MMC.